The Orbits—Anatomical Features in View of Innovative Surgical Methods - Cornelius, Carl-Peter; Mayer, Peter; Ehrenfeld, Michael; Metzger, Marc Christian (Facial Plastic Surgery, 2014)
The aim of this article is to update on anatomical key elements of the orbits in reference to surgical innovations. This is a selective literature review supplemented with the personal experience of the authors, using illustrations and photographs of anatomical dissections. The seven osseous components of the orbit can be conceptualized into a simple geometrical layout of a four-sided pyramid with the anterior aditus as a base and the posterior cone as apex. All neurovascular structures pass through bony openings in the sphenoid bone before diversification in the mid and anterior orbit. A set of landmarks such as the optic and maxillary strut comes into new focus. Within the topographical surfaces of the internal orbit the lazy S-shaped floor and the posteromedial bulge are principal determinants for the ocular globe position. The inferomedial orbital strut represents a discernible sagittal buttress. The periorbita and orbital soft tissue contents—extraocular muscles, septae, neurovasculature—are detailed and put into context with periorbital dissection.
Keywords: anatomy of internal orbit; osseous structures; bony surface contours; periorbita; extraocular muscles; connective tissue compartments; nerve and vessel supply